Crisis Narratives in International Law - Mbengue, Makane Moïse; D'Aspremont, Jean (Nijhoff Law Specials, 2021)
This volume offers a series of short and highly self-reflective essays by leading international lawyers on how global crises inform the functioning and theorizing of international law as well as how international law addresses global crises.; Readership: This book is of immediate interest to a readership of both scholars and practitioners, International lawyers, including scholars, practitionners, PhD students, postgraduate students and International Relations scholars